Food dyes as P-glycoprotein modulators. (December 2020) - Staples, Jack W.; Stine, Jessica M.; Mäki-Lohiluoma, Eero; Steed, Emily; George, Kathleen M.; Thompson, Charles M.; Woodahl, Erica L.
Abstract: The drug transporter P-glycoprotein (P-gp) is often investigated in drug-interaction studies because the activity is modulated by a wide variety of xenobiotics including drugs, herbal products, and food components. In this study, we tested six common arylsulfonate food dyes—allura red, carmoisine, ponceau 4R, quinolone yellow, sunset yellow, and tartrazine—as activators and inhibitors of P-gp activity in vitro . The dyes were studied as P-gp activators by measuring ATPase activity in P-gp-expressing membranes. Compared to verapamil, a known activator of P-gp, the six food dyes showed no stimulatory activity. The potential for these six food dyes to act as P-gp inhibitors was tested in an intracellular efflux assay with P-gp-expressing cells. Compared to GF120918, a known P-gp inhibitor, there was no inhibitory activity for these six food dyes. The six food dyes tested do not interact with P-gp in vitro and, therefore, are unlikely cause clinical drug-food dye interactions. Further investigation is necessary to determine whether these food dyes could interact with other drug transporters. Highlights: Consumption of food dyes may modulate clinically relevant xenobiotic transporters. Food-drug interactions with P-glycoprotein are important clinical considerations. Six arylsulfonate food dyes do not activate or inhibit P-glycoprotein in vitro .